2015
DOI: 10.1002/adfm.201502959
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Silicon Anodes for High‐Performance Lithium‐Ion Batteries

Abstract: Despite the high theoretical capacity of Si anodes, the electrochemical performance of Si anodes is hampered by severe volume changes during lithiation and delithiation, leading to poor cyclability and eventual electrode failure. Nanostructured silicon and its nanocomposite electrodes could overcome this problem holding back the deployment of Si anodes in lithium‐ion batteries (LIBs) by providing facile strain relaxation, short lithium diffusion distances, enhanced mass transport, and effective electrical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
167
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(176 citation statements)
references
References 259 publications
1
167
0
Order By: Relevance
“…24,25,41,130,149 Moreover, Si NWs in physical contact can weld together at their junctions by generating strong interfacial bonding after lithiation and delithiation. 41 The fusion at the Si NWs interfaces provides facile Li diffusion between surfacecontacted NWs, and may enable the self-assembly and self-healing of an interconnected network of Si NWs, because the detached NWs can still participate in Li storage after they form a robust interconnected network.…”
Section: Achievements Of the In Situ Tem Electrochemical Technique Inmentioning
confidence: 99%
See 3 more Smart Citations
“…24,25,41,130,149 Moreover, Si NWs in physical contact can weld together at their junctions by generating strong interfacial bonding after lithiation and delithiation. 41 The fusion at the Si NWs interfaces provides facile Li diffusion between surfacecontacted NWs, and may enable the self-assembly and self-healing of an interconnected network of Si NWs, because the detached NWs can still participate in Li storage after they form a robust interconnected network.…”
Section: Achievements Of the In Situ Tem Electrochemical Technique Inmentioning
confidence: 99%
“…The detrimental effect of the swelling may be mediated by formation of a coating like nickel (Ni) on silicon nanotubes (SiNTs), Si nanopillars, or yolk-shell-structured Si NPs. 24,51,68,162,163 Using functional Ni coatings or SiO x layers on the outer surface or both inside and outside of the SiNTs, with large hoop stress, the Si expanded inward toward the hollow inner core, instead of expansion outward or much less outward expansion. 162,164 However, Karki, et al, found that electrodes with negligible SiO x layer and significantly higher mass loading exhibit relatively low capacity-retention and faded quickly after early cycles.…”
Section: Achievements Of the In Situ Tem Electrochemical Technique Inmentioning
confidence: 99%
See 2 more Smart Citations
“…inTrODUcTiOn Lithium-ion batteries have been widely used in consumer electronics, electrical vehicles, and energy storage market (Tarascon and Armand, 2001;Chan et al, 2008;Li et al, 2009;Huang et al, 2013;Rahman et al, 2016). In recent years, lots of efforts have been put in exploring anode materials with higher specific capacities over graphite.…”
mentioning
confidence: 99%